As crenças dos professores de língua portuguesa sobre variação linguística - Sousa, Raquel Rodrigues (2023)
This study entitled -The beliefs of Portuguese language teachers about variation linguistics - is part of the line of research Constitution and Interpretation of Text and Discourse and is limited to the beliefs of Portuguese language teachers at state teaching schools Primary and secondary education in the state of Rondônia on the phenomenon of linguistic variation. O general objective was to investigate the beliefs of Portuguese language teachers in Rondônia about of the phenomenon of linguistic variation. The choice for this approach is justified by the need to deepen investigations into teachers’ beliefs and their implications in the school context, aiming to awaken in teachers understanding, flexibility and appreciation of linguistic varieties present in the classroom and in society as a whole. The theoretical foundation is delimited by Bagno (1999, 2001, 2007, 2014), Bortoni-Ricardo (2004, 2009, 2008, 2017, 2021), Faraco (2008, 2017), Luchese (2015), Santana (2014), antos (2019), Silva (2020) regarding linguistic variation in Brazil. As for the beliefs of teachers of foreign languages ​​and mother tongue in the Brazilian school context, this research is supported by Barcelos (1995, 2001, 2004) and Madeira (2015). The PCNs (2000), the LDB (1996), the Guidelines for Secondary Education (2007) (BNCC, 2017) and Theoretical Framework de Rondônia (2020) bring the laws that guarantee the topic is addressed in the classroom. Regarding the methodology, this is an exploratory, ibliographical research with a qualitative, developed through field research carried out with 61 language teachers Portuguese language in elementary and high school in state schools in Rondônia. This research provokes reflection on the influence of teachers' beliefs in the teaching of LM, a standard norm and the valorization of linguistic variation in the school context that aim to strengthen reflection, respect and recognition of each student’s culture. The results demonstrate that the beliefs of Portuguese language teachers are still strongly based on teaching of the standard norm as being the correct language, which must be worked on in the classroom with hard, even though some teachers perceived the need to also address the phenomenon of linguistic variation. It is clear, then, the need for continued training for LM teachers in the RO school context. The research is believed to have helped stimulate a more in-depth study of the beliefs of Portuguese language teachers in relation to linguistic variation and its pedagogical implications in the classroom, in order to carry out a I work with the Portuguese language that is most consistent with the language the student uses. Keywords: Beliefs. Linguistic variation. Standard norm. Teaching.